Australian Indigenous Knowledge and Libraries - Nakata, Martin; Langton, Marcia (UTS ePRESS, 2005)
In response to significant changes in the Indigenous information landscape, the State Library of New South Wales and Jumbunna Indigenous House of Learning at the University of Technology, Sydney, hosted a colloquium, Libraries and Indigenous Knowledge, in December 2004. The two-day colloquium brought together professionals, practitioners and academics to discuss future directions in relation to Indigenous knowledge and library services. An expert and inspiring group of speakers and more than 90 active participants ensured that lively discussions did, indeed, take place.